The fall of Gondolin - Tolkien, J. R. R. 1892-1973 (John Ronald Reuel); Tolkien, Christopher; Lee, Alan (Boston : Houghton Mifflin Harcourt, 2018)
"The final work of J.R.R. Tolkien's Middle-earth fiction, completing Christopher Tolkien's life-long achievement as the editor and curator of his father's manuscripts"--
Prologue -- The original tale -- The earliest text -- Turlin and the exiles of Gondolin -- The story told in the sketch of the mythology -- The story told in the Quenta Noldorinwa -- The last version -- The evolution of the story -- Conclusion.
Keywords: FICTION / Fantasy / Epic; FICTION / Fairy Tales, Folk Tales, Legends & Mythology; Fantasy fiction